Analisis Keputusan Pendanaan Pada Perbankan Syariah Di Indonesia - Mutamimah, Mutamimah; Fuadi, Firza (Jurnal Manajemen Bisnis, 2011)
This reasech aims to test the financing deciance at Sharia Banking. This excamination aims to answer the problem to what extend financing decision at Sharia Banking use Trade-off Theory or Packing Order Theory? The population of the research are sharia banking. The samples of this research consists of 5 sharia banks that are selected based on nonprobability technique with purpositive sanpling method. In processes testing the hypothesis was used Partial Last Square. Based on empiricial excamination result, it is generally concluded that financing decician at sharia banking prefer to use Trade-off Theory compared Packing Order Theory. Based on Trade Off Theory: non debt tax shields have impact negative to financing decision, liquidity have impact positive to financing decision. Based on Pecking order theory: probability have impact positive to financing decision, and investment have impact negative to financing decision.